Application of the Internet of Things in Banking Activities - Thu Trang, Dr. Nguyen Thi; Minh, Dr. Luong Xuan (Engineering And Technology Journal, 2024)
Internet of Things (IoT) technology has been of great interest in the banking sector in recent years. In order to keep up with digital transformation, commercial banks have been implementing many IoT projects, accelerating the digitalization process. The article is based on research on IoT, practical statistics in the industry and data at commercial banks in Vietnam. To understand IoT technology and how the banking industry approaches this technology. How has the Internet of Things helped commercial banks in the technology race and what benefits does it bring to customers using the service? In addition, the research paper also addresses the challenges that IoT is currently facing. Thereby, we propose a few recommendations to contribute to improving and solving those challenges.